2019
DOI: 10.1007/s00787-019-01334-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mental health improvement and deterioration in a large community sample of 11- to 13-year-olds

Abstract: Of children with mental health problems who access specialist help, 50% show reliable improvement on self-report measures at case closure and 10% reliable deterioration. To contextualise these figures it is necessary to consider rates of improvement for those in the general population. This study examined rates of reliable improvement/deterioration for children in a school sample over time. N = 9074 children (mean age 12; 52% female; 79% white) from 118 secondary schools across England provided self-report men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In the United Kingdom (U.K.), research has found that emotional problems such as anxiety and depression are the most common issues experienced by young people, followed by behavioural problems [ 2 ]. It is widely acknowledged that these difficulties may have a costly negative impact on educational attainment, drug use, criminality, physical health, poorer employment outcomes, not in education, employment or training (NEET) status, and financial difficulties [ 3 , 4 , 5 , 6 ]. The World Health Organisation (WHO) has called for a coordinated response from different sectors of society, noting that “among all the sectors that play critical roles in adolescent health, education is key” [ 7 ] (p. 8).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom (U.K.), research has found that emotional problems such as anxiety and depression are the most common issues experienced by young people, followed by behavioural problems [ 2 ]. It is widely acknowledged that these difficulties may have a costly negative impact on educational attainment, drug use, criminality, physical health, poorer employment outcomes, not in education, employment or training (NEET) status, and financial difficulties [ 3 , 4 , 5 , 6 ]. The World Health Organisation (WHO) has called for a coordinated response from different sectors of society, noting that “among all the sectors that play critical roles in adolescent health, education is key” [ 7 ] (p. 8).…”
Section: Introductionmentioning
confidence: 99%
“…This is an approach that has been used before and now forms the basis of analysis being considered in relation to child mental health outcomes for children seen across the National Health Service. 10,11 We hope this helps clarify the points raised. We would want to thank Professor Ford and Ms McManus again for engaging with us on this important topic in our shared aim to understand levels of mental health need in children and young people in order to determine how best to meet this need.…”
Section: Authors' Replymentioning
confidence: 91%
“…This is an approach that has been used before and now forms the basis of analysis being considered in relation to child mental health outcomes for children seen across the National Health Service. 10,11…”
mentioning
confidence: 99%
“…This finding is important and promising in the context of prevention as it demonstrates that students did not appear to experience the same level of deterioration in mental health at final follow-up that is often reported in other real-world studies of clinical and non-clinical samples of neurotypical young adolescents. The aforementioned synthesis of individual-level change in youth depression treatment outcomes found that 6% of young adolescents reliably deteriorated (Bear et al, 2020), and large trials in the United Kingdom found that 9-12% of adolescents reliably deteriorated (Warren et al, 2010;Wolpert et al, 2016Wolpert et al, , 2020. It is possible that the multilevel, strength-focused, resilience building features of RAP-ASD are responsible for this promising finding.…”
Section: Deterioration In Mental Health Reported For a Minority Of St...mentioning
confidence: 99%